Preparation of Students of Pedagogical Universities to Guide the Project-Research Activity of Pupils - Baymukhambetova, Botagoz; Nauryzbayeva, Elmira; Li, Elena; Baizhanova, Saule; Bekmagambetova, Maissara; Sapieva, Maira; Pchelkina, Tatyana (IEJME - MATHEMATICS EDUCATION, 2016)
The article is devoted to an actual problem of high school - preparation of students of pedagogical high schools to guide the project - research activity of pupils. On the basis of the research the author describes the creation of project - research sphere, which was carried out in three directions, each had certain problems. The first direction of work was aimed at developing students' methodological project and research knowledge and skills. The second direction was associated with the formation of the students' motivation - value attitude to project and research activity, and the active viewpoint on it. The third area of work was aimed at the development of personal qualities of a teacher-researcher. The main advantage of the given project - research sphere by the author is its sequence, continuity and consistency of the involvement of students in the project – research activity. Thus, activation of extracurricular project and research work of students contributes to the orientation of students to self-education, enabling students to be creative initiative, to apply the design and research knowledge into practice, to form the personality of a teacher-researcher.
Keywords: Project - research sphere; design - research activity; extracurricular work of students; methods of organization; the quality of professional training